Observation of oxygen ventilation into deep waters through targeted deployment of multiple Argo‐O2 floats in the north‐western Mediterranean Sea in 2013. Issue 8 (17th August 2017) - Coppola, L.; Prieur, L.; Taupier‐Letage, I.; Estournel, C.; Testor, P.; Lefevre, D.; Belamari, S.; LeReste, S.; Taillandier, V.
Abstract: During the winter 2013, an intense observation and monitoring was performed in the north‐western Mediterranean Sea to study deep water formation process that drives thermohaline circulation and biogeochemical processes (HYMEX SOP2 and DEWEX projects). To observe intensively and continuously the impact of deep convection on oxygen (O2 ) ventilation, an observation strategy was based on the enhancement of the Argo‐O2 floats to monitor the offshore dense water formation area (DWF) in the Gulf of Lion prior to and at the end of the convective period (December 2012 to April 2013). The intense O2 measurements performed through shipborne CTD casts and Argo‐O2 floats deployment revealed an O2 inventory rapidly impacted by mixed layer (ML) deepening on the month scale. The open‐sea convection in winter 2013 ventilated the deep waters from mid‐February to the end of May 2013. The newly ventilated dense water volume, based on an Apparent Oxygen Utilization (AOU) threshold, was estimated to be about 1.5 × 10 13 m 3 during the DWF episode, increasing the deep O2 concentrations from 196 to 205 µmol kg −1 in the north‐western basin. Key Points: Intense oxygen measurements were performed through Argo‐O2 floats in the north‐western Mediterranean Sea during convection events Ventilated dense water volume was estimated around 1.5 × 10 13 m 3 during the open‐sea convection process in winter 2013 Deep oxygen ventilation started in mid‐February and ended at the end of May 2013